Analisis Semiotika Pada Logo Batman 1966 - Tiara Zarismartha; San Ahdi (Universitas Katolik Widya Karya Malang, 2023)
Batman is a well-known superhero and is loved by many people from all walks of life, an interesting Batman character for not having superpowers like other superheroes. In addition to the character Batman has a striking logo and is an identity for Batman. In 1966 Batman released a series of films with decorative designated logos in which Pop Art's chests developed rapidly. Each logo is a visualized identity that has a meaning, using a qualitative method with Roland Barthes' semiotic analysis approach. The purpose of the study was to find out what values and meanings were cooped up in the 1966 Batman logo, which was influenced by the then-developed Pop Art style trend. Based on research results, it can be inferred that the use of the 1966 Batman logo influenced by Pop Art style and the visual elements of the logo suggests that the brief logo is an image and that Batman superhero has an intelligent, intellectual, optimistic nature of rooting out crime.